2020
DOI: 10.3389/fmicb.2020.585614
|View full text |Cite
|
Sign up to set email alerts
|

Proteome-Wide Analysis of Lysine 2-Hydroxyisobutyrylation in the Phytopathogenic Fungus Botrytis cinerea

Abstract: Posttranslational modifications (PTMs) of the whole proteome have become a hot topic in the research field of epigenetics, and an increasing number of PTM types have been identified and shown to play significant roles in different cellular processes. Protein lysine 2-hydroxyisobutyrylation (Khib) is a newly detected PTM, and the 2-hydroxyisobutyrylome has been identified in several species. Botrytis cinerea is recognized as one of the most destructive pathogens due to its broad host distribution and very large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 77 publications
1
16
0
Order By: Relevance
“…Khib is a newly discovered PTM reported in several species, such as mammals, plants, yeast, bacteria and fungi ( Huang et al, 2017 , 2018 ; Meng et al, 2017 ; Yin et al, 2019 ; Xu et al, 2020 ). In this research, Khib proteins were studied with proteome-wide analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Khib is a newly discovered PTM reported in several species, such as mammals, plants, yeast, bacteria and fungi ( Huang et al, 2017 , 2018 ; Meng et al, 2017 ; Yin et al, 2019 ; Xu et al, 2020 ). In this research, Khib proteins were studied with proteome-wide analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In U. virens , disruption of 2-hydroxyisobutyrylation in the MAPK pathway kinase UvSlt2 by mutation decreases fungal virulence ( Chen et al, 2021 ). In the comprehensive analysis of F. oxysporum , critical proteins for virulence – FoFmk1, FoHog1 and two MAP kinase signaling proteins – have been identified ( Qian et al, 2021 ); For B. cinerea , many 2-hydroxyisobutyrylated proteins are involved in substance synthesis and metabolism, redox and autophagy, kinase and protease, and are associated with the pathogenicity of B. cinerea ( Xu et al, 2020 ). However, similar studies on the peanut pathogen A. niger had not been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results further indicate that protein compositions, through their impacts on potential of PTMs such as protein ordering, could work together with genome structure to compensate for the evolutionary disadvantage of conserved genes such as eEF‐lα and other housekeeping genes in P. infestans in species. Indeed, it has been documented that protein disordering and many other PTMs can escalate the adaptation of species including pathogens to new environments independent of nucleotide variation (Brown et al., 2011; Nilsson et al., 2011; Volkwein et al., 2019; Xu et al., 2020; Yang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that this modification is evolutionarily conserved across bacteria, yeast, plants, animals, and humans on both histone and nonhistone proteins [1][2][3][4][5][6][7]. Recently, the 2-hydroxyisobutyrylomes of three filamentous fungi, namely, Ustilaginoidea virens, Botrytis cinerea, and Fusarium oxysporum, were also reported [8][9][10]. Khib adds a large 2-hydroxyisobutyryl group to the lysine residue, which increases the size of the lysine side chain, abolishes the positive charge, and introduces a hydroxyl group that enables the modified lysine to form hydrogen bonds with other molecules [1].…”
Section: Introductionmentioning
confidence: 99%